International Financial Statistics, October 2017. (International Financial Statistics; International Financial Statistics ;, 2017)
This paper discusses that for ease of comparison between the nominal effective exchange rate index and the real effective exchange rate index, the average exchange rate expressed in terms of US dollars per unit of each of the national currencies. In both cases, an increase in the index reflects an appreciation. Because of certain data-related limits, particularly where IMF estimates have been used, data users need to exercise considerable caution in interpreting movements in nominal effective and real effective exchange rates. The IMF publishes calculated effective exchange rates data only for countries that have given their approval. Similar indices that are calculated by country authorities may contain different results. For manufactured goods, trade by type of good and market is distinguished in the database. For primary products, the weights assigned depend principally on a country's role as a global supplier or buyer of the product.